2016
DOI: 10.1109/tifs.2016.2515505
|View full text |Cite
|
Sign up to set email alerts
|

Boosting 3D LBP-Based Face Recognition by Fusing Shape and Texture Descriptors on the Mesh

Abstract: Abstract-In this paper, we present a novel approach for fusing shape and texture local binary patterns (LBPs) on a mesh for 3D face recognition. Using a recently proposed framework, we compute LBP directly on the face mesh surface, then we construct a grid of the regions on the facial surface that can accommodate global and partial descriptions. Compared with its depth-image counterpart, our approach is distinguished by the following features: 1) inherits the intrinsic advantages of mesh surface (e.g., preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…The authors, point out procuced to interdependent instructions needs to provide higher accuracy result. N. Werghi, and et al [5] C. Tortorici Chang et al [6] accomplished 3D and 2D picture facial information merged score level based and data level considered to improve the performance to facial information. Both are concentrated 189 and 102 objects, used to found that 3D and 2D picture results in good identification attainment correlated to the 2Diamentional picture.…”
Section: \ Fig1 Block Diagram For Multimodal Fusion Methodsmentioning
confidence: 99%
“…The authors, point out procuced to interdependent instructions needs to provide higher accuracy result. N. Werghi, and et al [5] C. Tortorici Chang et al [6] accomplished 3D and 2D picture facial information merged score level based and data level considered to improve the performance to facial information. Both are concentrated 189 and 102 objects, used to found that 3D and 2D picture results in good identification attainment correlated to the 2Diamentional picture.…”
Section: \ Fig1 Block Diagram For Multimodal Fusion Methodsmentioning
confidence: 99%
“…To judge whether the detected human is the specific human (SH), his/her face is recognized by the FaceNet [19], which is one kind of face recognition [20]- [23]. FaceNet directly learns a mapping from face images to a compact Euclidean space where distances directly correspond to a measure of face similarity.…”
Section: Introductionmentioning
confidence: 99%
“…3D shapes make a wide array of new kinds of application possible, e.g., 3D biometrics, 3D medical imaging, 3D remote sensing, virtual reality, augmented reality, and 3D human-machine interaction [13]. As a special application of 3D shape analysis and processing, the key issue of 3D face recognition has also been widely addressed and identified to be much more robust to varying poses and illumination changes [14]. Therefore, pose invariant face recognition using 3D models is proving to be promising especially in case of in-depth pose variations along x-, y-, and z-axis under unconstrained acquisition scenarios of real world [15].…”
Section: Introductionmentioning
confidence: 99%
“…A prominent curve based method employing Riemannian framework is presented in the paper [26], whereas, the study [27] is a representative region based approach for occlusions and missing data handling problem. Hybrid approaches employ both of holistic and local feature-based methods [28] or combination of 2D and 3D images in the face recognition process [14].…”
Section: Introductionmentioning
confidence: 99%